The homo economicus under experimental attack - Ekkehart Schlicht (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2020)
For non-economists, it is often difficult to understand why economists place so much emphasis on the self-interest motive. It is obvious that people act out of a variety of motives - gratitude, anger, social obligation and many, many other motives. There are several reasons why economists still put the self-interest motive in the foreground. Three points of view seem particularly important: - homo economicus as a useful approximation - homo economicus as an ideal type - homo oeconomicus as as-if construction These justifications for the self-interest or homo-economicus assumption are briefly characterized.. It is explained why these justifications cannot be empirically disproved. Only their relevance can be questioned. Subsequently, the evolutionary point of view that underlies the as-if defense of homo economicus is radicalized and it is argued that it is appropriate to approach norm formation theoretically and experimentally from a psychological point of view.
urn:nbn:de:bvb:19-epub-74501-8
Keywords: D09; B13; B15; D01; 330; behavioral economics; rational choice; evolutionary economics; anomalies; bounded rationality; institutional economics; norm erosion